Students' Perception on the Use of Youtube Song Lyrics for Learning English - Yuhariah, Feti; Syafryadin, Syafryadin (JOLLT Journal of Languages and Language Teaching, 2023)
The objective of this research was to identify the Student’s perception to use youtube song for learning English at SMA 7 Kota Bengkulu. This study use quantitative method. The subject of this research was consisted of 28 students ten grade X IPA 8. In this research, the researcher used questioner to know the students perception to use youtube song for learning English. The result of this research, The result, 83% students gave positive respond in every activity conducted in the classroom because the song make the class become more conducive, fun, and meaningful, so it influenced their ability in listening improved well. Not only that, they also mastered the component of language in English, such as grammar, vocabulary, and pronunciation. The findings of the, learning English using YouTube while listening to English songs videos is more effective. The study demonstrated the value of YouTube songs as a learning tool for English.